Winter wheat (Triticum aestivum L.) mutation variability under chemical mutagenesis - Nazarenko , M. M.; Solohub , I. M. (Scientific Progress & Innovations, 2019)
The purpose of the article: the peculiarities of mutations’ induction under the influence of the chemical mutagen of 1,4-bisdiosoacetylbutane (DAB) on winter wheat varieties Favorytka, Lasunia, Khurtovyna, Kolos Myronivshchyny, Sonechko, Kalynova, Voloshkova, and line 418 were investigated. Methods of research. Determining the frequency of mutations in field conditions and the level of variability under the action of DAB. The research results. The variability of the mutation frequency depending on the concentration of DAB (1.4-bisdiosoacetylbutane) (0.1, 0.2 %) and on the mutagen-genotype interaction has been established. It was shown that in all genotypes the highest frequency of mutations has been observed at DAB action at the concentration of 0.2 %. The variation range of the mutations frequency at the indicated concentration from 2.8 % (Kalynova variety) to 14.0 % (Sonechko variety) was determined. The using of DAB to obtain economically-valuable mutations had the limited value. Reducing the frequency and narrowing the spectrum of mutations at the repeated action of the chemical mutagen has been established. The elements of scientific novelty. Further development of the idea about the possibilities of valuable mutation induction rates has been acquired. New donors of valuable traits for breeding researches have been discovered. Practical value. The peculiarities of induction peculiarities of some mutation types in soft winter wheat have been established. Key words: winter wheat, 1.4-bisdiosoacetylbutane, chemical mutagenesis, mutations. Statement of the problem. The peculiarities of the chemical mutagen action and the induction of mutations during their interaction with the genotype of eight varieties and lines of winter wheat have been investigated. Chemical mutagenesis, in spite of significant methodological and practical difficulties, has significant advantages as a more site-specific method. Using the chemical mutagens, it is possible to forecast the probability of occurring certain types and groups of mutations with a higher probability than after the action of physical mutagens. Therefore, detecting the spectrum of possibilities of DAB chemical mutagen in inducing genetically valuable mutations is an urgent task. The purpose of the research was to study the optimization peculiarities of the system mutagen – concentration of mutagen – genotype of initial form to forecast the mutagen action consequences under DAB action in order to raise the number of economically- and genetically-valuable mutations. The research task was to analyze the rate and spectrum of mutations of winter wheat plants under the influence of some DAB concentrations, select breeding and genetically valuable mutant lines for further using, to identify possible deviations ay mutagen action depending on the method of obtaining varieties. Materials and methods of research. The seeds of following varieties of winter wheat have been treated by mutagens Favorytka, Lasunia, Khurtovyna, line 418, Kolos Myronivshchyny, Sonechko, Kalynova, Voloshkova. We used DAB chemical mutagen (1.4-bisdiosoacetylbutane) in concentrations 0.1, 0.2 %). The experiment was conducted in the Scientific-Educational Centre of DSAEU. In 2011–2012 we identified the mutations with phenological observations and by yield and yield structure (1–3 rows trials, inter-row - 0.15 m, the row length - 1.5 m), and the variety after every 10–20 trials was initially as check. In 2013–2017 the character of heredity was investigated, the yield component analysis was conducted on 30 plants at М4–М6 generations. The research results. The total number of families in the second generation after mutagen treatment was 8000. Mutations were detected by phenological observations and accounting in M2–M3, followed by checking inheritance. Depending on the concentration of the mutagen, the mutation rate ranged from 2.8 % (Kalynova variety) to 14.0 % (Sonechko variety). The highest mutation rate was observed at mutagen concentration of 0.2 %. In general, the highest mutation rate was characteristic of winter wheat varieties obtained by the methods of hybridization and thermo-mutagenesis. In the general spectrum of mutations, 33 traits were identified, according to which changes occurred under the action of dimethyl sulfate. For analysis, these characters were combined into groups: structural mutations of the stem and leaves; the intensity of the wax coating; color mutations and structure of the ear; color mutations and grain structure; mutations according to the physiological signs of growth and development; system mutations; mutant families. It has been established that a characteristic distinguishing feature of DAB was the absence of systemic mutations, dwarfs, and almost the absence of sterile plants and mutants by spike structure. The following mutations were considered as valuable – short-stemmed, semi-dwarfs, large spike, large grains, early-maturing, productive plants. Altogether 5 short-stemmed, 2 semi-dwarf, 2 having a large spike, 1 having large grains, and 3 early-maturing mutations were obtained. The mutant lines with increased grain yield were identified at 0.1 % DAB concentration. Their number varied from 0 to 0.2 % in the variant. The only exception was Lasunia variety mutant, at the DAB 0.1 % (line 174 in further testing), which showed a high weight of grain from a plant and in some years exceeded the standard concerning the yield, in addition, this line had a higher complex resistance to diseases. Conclusions. For DAB as a mutagen, the genotype-mutagenic effect is significant when the varieties obtained by the action of chemical mutagenesis (Kalynova) were taken. DAB, as a mutagen, had a much weaker effect on Kalynova variety that was created when using this mutagen. The effect of DAB was again confirmed by the high site-specificity of chemical mutagens. The frequency of mutations and the level of variability were significantly lower than at other mutagens. The mutant lines with increased grain productivity were identified at 0.1% DAB concentration. The number of them varied from 0 to 0.2 % in the variant. At further testing, nearly all of these forms were discarded. A small number of economically valuable mutations was detected.